2019
DOI: 10.1155/2019/2523032
|View full text |Cite|
|
Sign up to set email alerts
|

miR-509-5p Inhibits the Proliferation and Invasion of Osteosarcoma by Targeting TRIB2

Abstract: Osteosarcoma (OS) is one of the most common malignant bone tumors in adolescents with a poor prognosis. Though miR-509-5p has been reported as a tumor suppressor in several human cancers, the role of miR-509-5p in OS remains unclear. In this study, our result of real-time PCR (RT-PCR) showed that the expression of miR-509-5p was significantly decreased in OS tissues and cell lines. Overexpression of miR-509-5p significantly suppressed cell proliferation and invasion in OS cell lines. Moreover, we identified tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…This study shows that miR-206 and miR-140 target the transcription factor phospho-Smad3 which, in turn, binds CAGACA sequences in TRIB2 promoter. In line with this data, in osteosarcoma tissues and cell lines, TRIB2 is a direct target of miR-509-5p and when miR-509-5p is overexpressed or TRIB2 is silenced, the malignant capacity of osteosarcoma cells, in terms of proliferation and invasion, its reduced [ 103 ]. Additionally, TRIB2 stability could be target by modifying Ubiquitin E3 ligase SCF β-TRCP levels.…”
Section: Targeting Trib2mentioning
confidence: 86%
“…This study shows that miR-206 and miR-140 target the transcription factor phospho-Smad3 which, in turn, binds CAGACA sequences in TRIB2 promoter. In line with this data, in osteosarcoma tissues and cell lines, TRIB2 is a direct target of miR-509-5p and when miR-509-5p is overexpressed or TRIB2 is silenced, the malignant capacity of osteosarcoma cells, in terms of proliferation and invasion, its reduced [ 103 ]. Additionally, TRIB2 stability could be target by modifying Ubiquitin E3 ligase SCF β-TRCP levels.…”
Section: Targeting Trib2mentioning
confidence: 86%
“…Also, miR-509 as epithelial-mesenchymal transition miRNA was shown to induce the expression of E-cadherin, and inhibit cell motility and invasion 52 . In addition, miR-509 can inhibit cell motility and invasion through targeting tribbles pseudokinase 2 ( TRIB2) in osteosarcoma 53 . Our findings showed that miR-509 was significantly down-regulated in tumor tissues in comparison with their adjacent non-tumoral tissues, and lower miR-509 expression in tumoral tissues was associated with high tumor grade, stage, and H. pylori infection.…”
Section: Resultsmentioning
confidence: 99%
“…Trib2 is a cancer-associated pseudokinase that can be induced by mitogens and enhances the propagation of several cancer cells, including myeloid leukemia, liver, lung, skin, bone, brain, and pancreatic [ 10 , 46 ] (Table 1 ).…”
Section: Different Roles Of Trib2 In Tumorigenesismentioning
confidence: 99%